Why are cognitive test scores of Spanish adults so low? The role of schooling and socioeconomic background. Issue 4 (4th July 2022) - Anghel, Brindusa; Cuadrado, Pilar; Tagliati, Federico
ABSTRACT: We explore the cognitive skill gap between the adult population in Spain and in the rest of European Union countries using the Program for the International Assessment of Adult Competencies. We find that differences in schooling account for about a third of the average difference in cognitive test scores, whereas differences in socioeconomic background explain about one fourth of the average score gap. While cognitive skill gaps are increasing across the distribution of test scores, differences in educational stocks and socioeconomic factors explain a larger fraction of the gap at the bottom than at the top of the skill distribution.